The Effect of Ethanol on the Compound Thresholds and Aroma Perception in Chinese Baijiu - Jialing Lu; Jia Zheng; Dong Zhao; Yan Xu; Shuang Chen (Molecules)
Strong-aroma type Baijiu and its diluted samples were characterized through descriptive analysis. Significant changes were observed in four (ethanol, Jiao-aroma, fruity, and grain) of the nine aroma attributes, primarily attributed to variations in ethanol concentration rather than other compounds. The thresholds of 40 compounds in aqueous solutions with alcohol concentrations of 20%, 30%, 40%, 50%, and 60% were measured using three-alternative forced-choice tests. The thresholds of 30 compounds were significantly positively correlated with ethanol concentration. The thresholds of 40 compounds were affected by ethanol concentration to varying degrees, with changes ranging from 2 to 692 times. Due to the varying degrees of alcohol influence on the compound threshold, the aroma profile of diluted Baijiu sample is different from the original Baijiu sample.